Translation, adaptation, and initial evaluation of a guided self-help intervention to reduce psychological distress among nurses during COVID-19 in China - Tian, Tian; Sun, Jingwen; Jiang, Yue; Guo, Qian; Huang, Zeyu; Wang, Duolao; Rahman, Atif; Li, Xiaomei; Yang, Lei (Frontiers in Psychiatry, 2023)
Background: To reduce the unprecedented and intense psychological distress that nurses were forced to experience during the COVID-19 pandemic, a Chinese version of the World Health Organization's Self-Help Plus (SH+) intervention guide was adapted and tested among nurses. The objective of this study was to translate and adapt the SH+ guideline into the Chinese version and to test its feasibility in reducing psychological distress among nurses during COVID-19. Methods: A staged approach comprising translation, adaptations, initial evaluation by pilot implementation, and a qualitative process evaluation was conducted in two hospitals in Xi’an, China. The translation of the Chinese version was authorized by the World Health Organization. We adapted SH+ for use among clinical nurses working during the pandemic in China through a qualitative process evaluation, which was guided by the descriptive phenomenological study design. The outcomes of the pilot included the psychological distress, psychological flexibility, depressive and anxiety symptoms, post-traumatic stress disorder (PTSD) symptoms, and subjective psychological well-being, that were assessed using the Kessler 6 symptom checklist, the Comprehensive Assessment of ACT Process (CompACT), the Patient Health Questionnaire-9 (PHQ-9), the Generalized Anxiety Disorder scale (GAD-7), the PTSD Checklist - Civilian Version (PCL-C) and the Index of Well-Being (IWB), respectively. Results: The SH+ materials, including audio-recorded sessions and an accompanying illustrated manual, were translated into Chinese and adapted in line with feedback from the nurses. An uncontrolled pilot study (n = 28) for 5 weeks showed a statistically significant reduction of psychological distress (mean difference in Kessler 6 score, -2.74; 95% CI [-3.71, -1.78]; p < .001). We also found improvements in psychological ﬂexibility (mean difference in CompACT (p < .001), subjective psychological well-being (p < .05), and depressive symptoms (p < .05). The process evaluation showed that nurses found the SH+ program very useful but difficult to adhere to. Conclusions: We found that the translated Chinese version of SH+ was applicable and feasible in the Chinese cultural context. There was a potential effect of adapted SH + in reducing nurses' psychological distress during COVID-19 and suggested the value of exploring strategies to increase adherence to the program.